2005
DOI: 10.1007/s11104-004-0159-x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microorganisms: An Important Determinant of Allelopathic Activity

Abstract: Current evidence illustrates the significance of soil microbes in influencing the bioavailability of allelochemicals. This review discusses (i) the significance of soil microorganisms in influencing allelopathic expression, (ii) different ways of avoiding microbial degradation of putative allelochemicals, and (iii) the need of incorporating experiments on microbial modification of allelochemicals in laboratory bioassays for allelopathy. Several climatic and edaphic factors affect the soil microflora; therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
135
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(140 citation statements)
references
References 79 publications
1
135
0
4
Order By: Relevance
“…However, relative concentrations of some phenolics may increase during decomposition depending upon their chemical structure (Gallet and Lebreton 1995), and moreover the ability of microbes to metabolize those structures (Sugai and Schimel 1993). In fact, it has been well demonstrated that microbial metabolism is an important factor in determining the magnitude and duration of allelopathic interactions involving phenolic acids as soil microorganism are both producers and degraders of chemicals and are in the same time affected by allelochemicals (Inderjit 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, relative concentrations of some phenolics may increase during decomposition depending upon their chemical structure (Gallet and Lebreton 1995), and moreover the ability of microbes to metabolize those structures (Sugai and Schimel 1993). In fact, it has been well demonstrated that microbial metabolism is an important factor in determining the magnitude and duration of allelopathic interactions involving phenolic acids as soil microorganism are both producers and degraders of chemicals and are in the same time affected by allelochemicals (Inderjit 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Other workers have also demonstrated that soil properties can greatly affect allelopathy phenomena in various ways (Tongma et al, 2001;Hiradate et al, 2010). Different effects of N is probably due to its different influences on the microbes which decompose plant materials, as each one has its own specific microorganism capable of degrading its plant material (Kumar et al, 1993;Schmidt and Lipson, 2004;Inderjit, 2005;Xuan et al, 2005). The C/N ratio of the allelopathic crop materials is another important factor which can influence the rate of the release of allelochemicals into the soil and consequently their inhibitory effects on germination and seedling growth of weeds.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike artificial herbicides, the use of allelopathy for weed suppression in agroecosystems is a complicated practice. A broad range of different factors can influence the allelopathic activity of allelochemicals, including soil and climatic conditions (Ponder et al, 1985;Blum, 1998;Kobayashi, 2004;Inderjit, 2005). Nevertheless, there is not a lot of works describing the inhibitory effects of allelopathic plant materials as influenced by soil factors.…”
Section: Introductionmentioning
confidence: 99%
“…A controlled laboratory microcosm approach can allow for isolation of the chemical effects of mulch residue, where aqueous extracts can be used to simulate allelochemical leachate. The inclusion of soil in allelopathic microcosms to account for microbial degradation and other interactions with soil is an important factor often overlooked in allelopathy studies [8] [9].…”
Section: Introductionmentioning
confidence: 99%